Comparative Study of Plaque pH Response to Non-Fermentable Sugar in Caries-Free Children and Adults - Naseemoon Shaik; Vivek Buddha; Krishna Priya Vellore; Vidya Priyadarshini; Tirumala Ravali Cheduravally; Kavya Pala (Journal of Pharmacy and Bioallied Sciences)
Background: Effective caries prevention relies on understanding oral pH regulation (Stephan curve) during fermentable carbohydrate challenges. Saliva and plaque fluid buffering systems play a crucial role, but their composition, secretion rate, and buffering capacity vary with age, affecting pH regulation over time. Aim: To evaluate plaque pH changes over a period of 30 min post-challenge of distilled water and 10% stevia in children (4–6 years), young adult (22–25 years). Methodology: Consented 20 children and 20 young adults refrained from tooth brushing for 48 hours. Subjects from each age group were randomly divided into two groups, namely control and stevia. After evaluating baseline saliva and plaque pH, the subjects were asked to rinse thoroughly with 15 mL of the test drinks for a period of 30 s. Post-rinse at 5, 10, 15, 20, 25, and 30 plaque pH of each sample was measured. pH curves were constructed using the mean plaque pH readings of test drink and compared. Results: Children exhibited higher baseline plaque pH and more effective pH recovery compared to adults across test groups (control and stevia). In the stevia group, children maintained higher pH values at all time points, highlighting superior buffering capacity in children compared to adults. Conclusion: Within the limitation of this study, a significant variation was observed in pH regulation system of children compared to adults, and in children, the pH was better regulated.